FAKTOR IKLIM KERJA DAN PERAN KEPALA SEKOLAH DALAM KEPUASAN KERJA GURU SEKOLAH DASAR KAJIAN LITERATUR - Budi, Tulus; Nuni Widiarti; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher job satisfaction is an important factor influencing the quality of education, particularly at the elementary school level. This study aims to examine the influence of work climate and the role of principals on teacher job satisfaction through a systematic literature review (SLR). The method used in this study is a qualitative descriptive approach by reviewing relevant articles published between 2020–2025. The data sources were obtained from several national journals focusing on educational management, leadership, and teacher performance. The results show that a positive work climate significantly contributes to improving teacher job satisfaction. In addition, the principal's leadership role, including managerial competence, supervision, and motivation, has a direct and indirect effect on teacher satisfaction. The synergy between a conducive work climate and effective school leadership creates a supportive environment for teachers to perform optimally. Therefore, strengthening organizational climate and principal leadership is essential to enhance teacher job satisfaction in elementary schools.